2019
DOI: 10.1177/1060028019873320
|View full text |Cite
|
Sign up to set email alerts
|

Brexanolone (Zulresso): Finally, an FDA-Approved Treatment for Postpartum Depression

Abstract: Objective: To review the safety and efficacy of brexanolone for the treatment of moderate to severe postpartum depression (PPD). Data Sources: A literature search through PubMed was conducted (January 2012 to July 2019) using the keyword brexanolone for clinical trials published in the English language. Study Selection and Data Extraction: Articles were selected if they were related to the Food and Drug Administration (FDA) approval of brexanolone or provided novel clinical information regarding this drug enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Downstream enzymes including 5α-reductase and 3α-hydroxysteroid dehydrogenase then catalyze the conversion of the hormones into other types of neuroactive steroids. Allopregnanolone, a 5α-reduced progesterone metabolite synthesized by the brain, was recently approved by the U.S. Food and Drug Administration (FDA) as Zulresso™ for treatment of postpartum depression (196). It is a strong positive allosteric GABA A receptor modulator and is deficient in patients with depression (243) (52).…”
Section: Sex Steroidsmentioning
confidence: 99%
“…Downstream enzymes including 5α-reductase and 3α-hydroxysteroid dehydrogenase then catalyze the conversion of the hormones into other types of neuroactive steroids. Allopregnanolone, a 5α-reduced progesterone metabolite synthesized by the brain, was recently approved by the U.S. Food and Drug Administration (FDA) as Zulresso™ for treatment of postpartum depression (196). It is a strong positive allosteric GABA A receptor modulator and is deficient in patients with depression (243) (52).…”
Section: Sex Steroidsmentioning
confidence: 99%
“…It has been reported that ALLO is an allosteric regulator of GABA receptors playing a role in depression and anxiety [33], as well as a variety of neurodegenerative diseases such as diabetic neuropathy [34], Alzheimer's disease [35] and Parkinson's disease [36]. It has been investigated for the treatment of Severe Postpartum Depression as the main ingredient of Zulresso (the rst FDA-authorized PPD inhibitor) [37]. Eminently, our nding is the rst time revealing the novel pharmacological activity of ALLO against in uenza virus with broad-spectrum and identi ed ALLO playing an antiviral role in the replication period in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, using risk factors for MDD with peripartum onset, such as low levels of social support and a history of depression, could help with starting interventions early on with high-risk patients [12]. Finally, neurosteroids, such as brexanolone, are a promising approach to treating MDD with peripartum onset; further research into this class of compounds may lead to the discovery of more efficacious treatments for MDD with peripartum onset [13].…”
Section: Discussionmentioning
confidence: 99%